Does the low-carbon city policy make a difference? Empirical evidence of the pilot scheme in China with DEA and PSM-DID - Yang Fu (Elsevier, 2021)
The pilot scheme of low-carbon cities was first introduced in 2006 in China and now three rounds of over a hundred cities have been listed as pilots. There have been studies arguing that the policy has significantly reduced carbon emission in the pilot cities. However, with greater policy leverage and resource input, it is not difficult for the pilot cities to reduce their overall carbon emissions. The more important question is: Do the low-carbon cities reduce carbon emission efficiently considering various input and output indicators? Does the policy really make a difference by reducing carbon emission at the city level from a cost-effectiveness perspective? This research addresses the gap by introducing the Malmquist-Luenberger productivity index in DEA and the quasi-experimental method of Difference in Difference with Propensity Score Matching (PSM-DID) to evaluate the impacts of the low-carbon city pilot scheme in China. Beyond the results that the policy did improve the overall carbon emission efficiency of pilot cities, the article generates several intriguing findings: (1) Although existing researches argue that the policy helps reduce the carbon emission of pilot cities immediately, our findings suggest that it takes longer time to improve the carbon emission efficiency; (2) The proportion of secondary industry and energy intensity of the cities are negatively related to the carbon emission efficiency while capital-labor ratio and the investment in research work the other way around; (3) The policy might further deepen the urban divide between the eastern and western regions since it is more effective on eastern pilot cities; and (4) The mechanisms through which the policy takes effects have also been discussed.